Indonesian In The Emerging Global Knowledge Economy:Demand Side Pressures to Upgrade - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
The global economic context within which Indonesia has been able to grow rapidly over the past 30 year period is expected to be significantly different to that in the next 30 years. While there are a host of factors expected to contribute to this change, there is perhaps none more fundamental than the combined effect of the trend toward international economic deregulation and the ongoing revolution in information and communications technologies, leading to the emergence of what many refer to as the global knowledge economy. An important implication of the emergence of the global knowledge economy is a fundamental transformation in consumption and production activities all over the world. This in turn suggests that demand conditions in international trade should be changing rapidly in favor of more knowledge intensive products and industries. Thus, orientation to world demand growth can represent a useful indicator of a particular country's ability to participate in the g16 bat knowledge economy. The first section of this paper will measure Indonesian export orientation to world demand growth as a means to assess the challenge posed by changing global conditions to the Indonesian economy, and also to assess Indonesia's comparative performance within those changing circumstances over the1980-95 period. The results of the empirical analysis in this section suggest that Indonesia has been improving its orientation toward high growth industries, particularly in the post-deregulation period, but nevertheless continues N exhibit a less dynamic export structure than most other countries in the region. The second section provides a more qualitative analysis of those demand side pressures which compel low wage and commodity exporting countries such as Indonesia to upgrade to more knowledge intensive activities. These include international trends which